APOPTOSIS AND NECROSIS - PROGRAMMED CELL DEATH AND ITS ROLE IN CELL LIFE ACTIVITY - Uzoqova Sh.S; Sattorova I.Ya; Cho’liyev I.N. (Journals Park Publishing, 2022)
This article is devoted to programmed cell death - apoptosis. Death occurs after the cell has performed all its vital functions in an apoptotic manner. This is a natural process. In doing so, the molecules that make up the cell structure are gradually broken down into parts, allowing other cells in the same organism to use them. Apoptosis cannot be equated with necrosis at all. In apoptosis, cell-killing software — genes — work. Apoptosis is the programmed death of a cell that is controlled by self-killing genes. The process of apoptosis is not rapid and is different from necrosis. First the mitochondria then the nucleus and finally the cytoplasm breaks down into fragments, i.e. the cell divides into fragments and apoptotic bodies are formed, which are phagocytosed or dissolved by macrophages. Apoptosis as an immunomodulatory form of cell death plays a stabilizing role in maintaining the number of cells in the body. Although much information and evidence has been provided about apoptosis, there is insufficient information on the role of mitochondria in their origin. Therefore, this article provides information on the impact of impaired mitochondrial dysfunction on the development of cell-programmed death - apoptosis.
Keywords: cell; mitochondria; nucleus